Comparison between time, spectral and wavelet analysis on wave breaking and propagation - Conde, J. M. (2014)
The present work focuses on the comparison between three types of data analysis (time analysis; Fourier transform spectral analysis; and wavelet transform spectral analysis) applied to different types of waves (monochromatic, bichromatic and irregular). The main objective is to study experimentally wave shoaling and breaking over a set of different gentle slopes for several incident waves. The data and results from time, Fourier and wavelet analysis presented include: free surface elevation along the flume and the corresponding amplitude spectra; significant wave height, Hs, and significant wave period, Ts, along the flume.